2008
DOI: 10.1152/ajpheart.91491.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential arterial blood flow response of splanchnic and renal organs during low-intensity cycling exercise in women

Abstract: To investigate the regional hemodynamic responses of abdominal arteries at the onset of exercise and to focus on their transient responses, eight female subjects (21-30 yr) performed ergometer cycling exercise at 40 W for 4 min in a semi-supine position. Mean blood velocities (MBVs) in the right renal (RA), superior mesenteric (SMA), and splenic (SA) arteries were measured by pulsed echo-Doppler ultrasonography, with beat-by-beat measurements of heart rate (HR) and mean arterial pressure (MAP). The vascular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…Baseline vessel measurements obtained here were in agreement with those reported in the literature for flow 20,27,28 and velocity, 20,27,29 and the CV for SMA, HA, and SA are consistent with those reported for the renal artery. 30 Dambreville et al 30 also…”
Section: Discussionsupporting
confidence: 91%
“…Baseline vessel measurements obtained here were in agreement with those reported in the literature for flow 20,27,28 and velocity, 20,27,29 and the CV for SMA, HA, and SA are consistent with those reported for the renal artery. 30 Dambreville et al 30 also…”
Section: Discussionsupporting
confidence: 91%
“…One study found that the blood flow decreased by 30% in the SMA, whereas it decreased by 50% in the CA during dynamic exercise at 75% V ・ O2max 12) . In another study, the blood flow decreased by 30% in the spleen, but not in the SMA, during light-intensity exercise 4) . It appears reasonable to assume that non-uniform responses in the splanchnic blood flow are controlled multifactorially by the autonomic, humoral, and local organ-specific regulatory systems.…”
Section: Splanchnic Blood-flow Response To Exercisementioning
confidence: 88%
“…Renal flow decreases proportionally with increasing exercise intensity via vasoconstriction [1][2][3] , while cardiac output increases up to fivefold of the resting value in exercising humans 3) . Even light-intensity exercise decreased renal flow by 20% within 30 s of exercise onset 4) . In addition, during exercise the blood flow increases in organs other than exercising muscles.…”
Section: Introductionmentioning
confidence: 98%
“…The details were described in our previous study. 18 The vascular conductance (VC) of the brachial artery was calculated as the ratio of each blood flow to MAP.…”
Section: Methodsmentioning
confidence: 99%